Letter in response to correspondence on ‘Conceptualisation of the characteristics of advanced practitioners in the medical radiation professions’ - Kane, Paul (J Med Radiat Sci, 2015)
There is ongoing debate on the position of research as an attribute of advanced practice. This letter highlights some issues to be considered in light of recent correspondence published in the JMRS.[Image: see text]